HIV infection among family planning clinic attenders in Glasgow: why prevalence has remained low in this general population group. Issue 1 (February 1998) - Goldberg, D; Carr, S; Cameron, S; Codere, G
Abstract : OBJECTIVE: During 1991-2, unlinked anonymous testing of dried blood spots from neonatal metabolic screening cards showed the prevalence of HIV among childbearing women from Glasgow to be extremely low at 0.01%. A study was conducted to determine if non-pregnant sexually active women who engaged in unprotected sexual intercourse were more likely to be infected than those who were pregnant. METHODS: Unlinked anonymous HIV testing of urine specimens submitted by attenders of the family planning clinic in Glasgow for pregnancy testing. RESULTS: Of 11, 990 urine specimens tested, 7664 were from women with a negative pregnancy test and two of these were HIV positive (0.026%); none of the remainder from those with a positive pregnancy test had HIV antibodies. CONCLUSION: No hidden epidemic was unearthed among a population which had engaged in unprotected sexual intercourse and was not pregnant. Other data from Glasgow strongly suggest that the control of HIV transmission among the city's population of current injectors (HIV prevalence, 1% of 8500) has prevented the spread of infection into its wider heterosexual population. It is essential that preventive measures which have been responsible for this public health success should be maintained.